2014
DOI: 10.1044/2014_jslhr-l-13-0228
|View full text |Cite
|
Sign up to set email alerts
|

Dialect Awareness and Lexical Comprehension of Mainstream American English in African American English–Speaking Children

Abstract: Purpose This study was designed to examine the relationships among minority dialect use, language ability, and young AAE-speaking children’s understanding and awareness of MAE. Methods 83 4- to 8-year-old African American English-speaking children participated in two experimental tasks. One task evaluated their awareness of differences between Mainstream American English (MAE) and African American English (AAE), while the other evaluated their lexical comprehension of MAE in contexts that were ambiguous in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 29 publications
3
32
1
Order By: Relevance
“…Speakers vary in the extent to which they use AAE features and the extent to which they are familiar with the mainstream dialect, and this variability should modulate any dialect-related effects. For example, Edwards et al ( 2014 ) found that dialect density predicted children's comprehension of words spoken in MAE, and Charity et al ( 2004 ) found that children's accuracy imitating MAE forms was a reliable predictor of their scores on standardized measures of early reading abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Speakers vary in the extent to which they use AAE features and the extent to which they are familiar with the mainstream dialect, and this variability should modulate any dialect-related effects. For example, Edwards et al ( 2014 ) found that dialect density predicted children's comprehension of words spoken in MAE, and Charity et al ( 2004 ) found that children's accuracy imitating MAE forms was a reliable predictor of their scores on standardized measures of early reading abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Preservice teachers are likely to enter school with negative attitudes toward AAVE (Newkirk-Turner, Williams, Harris, & McDaniels, 2013), classroom teachers are likely to treat AAVE features in a text as errors to be corrected (Dyson & Smitherman, 2009), and when students are formally assessed, their failure to suppress AAVE features may be penalized (D. Johnson & VanBrackle, 2012). Conversely, students who speak AAVE may bear additional cognitive burdens as they read Standard American English texts, or codeswitch to suppress AAVE features in their writing (Edwards et al, 2014). The situation is compounded by the fact that use of AAVE is strongly linked to African American identity.…”
Section: Group Differences That May Affect Language and Transcriptionmentioning
confidence: 99%
“…The final assessment for the TALK program was an experimental measure of lexical comprehension of MAE (Edwards et al, 2014). In brief, the lexical comprehension task examined children's ability to understand words that were ambiguous in AAE, but unambiguous in MAE.…”
Section: Assessmentsmentioning
confidence: 99%
“…Last, there is considerable evidence that it is more difficult for adult listeners to process an unfamiliar dialect, particularly in noise (Clopper, 2012;Clopper & Bradlow, 2008). Both Harris and Schroeder (2013) and Edwards et al (2014) proposed that such findings suggest that dialect mismatch will put non-MAE (NMAE) speakers at a disadvantage: In the noisy classroom environment, they need to expend additional cognitive resources simply to understand their teacher.…”
mentioning
confidence: 99%
See 1 more Smart Citation